Account-to-account electronic money transfers: Recent developments in the United States - Oz Shy (Federal Reserve Bank of Boston, 2011)
This paper reviews recent developments in online and mobile banking in the United States that provide bank account holders with low-cost interfaces to manage account-to-account electronic money transfers. The paper analyzes the emerging decentralized market in which A2A money transfers are becoming available in the United States and compares it with the A2A market in other countries. The paper constructs analytical examples to explain and evaluate the structure of the emerging U.S. market and discusses possible policy actions that may enhance the use of A2A money transfers in the United States.
Keywords: E42; G29; D14; 330; account-to-account money transfers; person-to-person money transfers; online banking; mobile banking; payment networks